Revolution day the human story of the battle in Iraq - Omaar, Rageh 1967- (Viking, an imprint of Penguin Books Ltd, 2004)
The author reported from Iraq for six years prior to the conflict in 2003. He evaded the official minders to meet ordinary Iraqis, finding out how they lived under Saddam's brutal regime. His account of the war years, the siege, deprivation and destruction, are told by a knowledgeable insider